STRATEGI PENGEMBANGAN WARALABA BERBASIS E-COMMERCE: PELUANG TANTANGAN di ERA DIGITAL - Patricia, Rachel Anne; i, Urbanisasi (Peneliti.net, 2023)
In the increasingly advanced digital era, e-commerce-based franchise development strategies have become the focus of the business world. The purpose of this study is to analyze the opportunities and challenges faced by franchise companies when using electronic platforms to develop their business. In the legal context, this study also analyzes relevant legal issues in the development of e-commerce-based franchising, including e-franchise agreements, trademark protection, personal data protection, privacy practices, consumer protection and other legal aspects that must be considered. in implementing this strategy. This study aims to analyze the opportunities and challenges faced by franchise companies in using electronic platforms to develop their business. The increasingly advanced digital era has opened up new opportunities for franchise companies to utilize e-commerce as a means to reach a wider market. However, while benefiting from electronic platforms, franchise companies also face a number of legal challenges that need to be understood and addressed.